Documentation and physical interpretation of the African monsoon intra-seasonal variability for improved weather forecasts - (:unkn) unknown (My University, 2013)
The West African monsoon rainfall experiences a large spatial and temporal variability. In this thesis, a focus has been given on the synoptic to intra-seasonal scales which can lead to dramatic socio-economic consequences over Sahelian areas. The main goal is, on the one hand, to document and hence to better understand the physics associated with such scales of variability, and on the other hand, to provide some useful tools to improve short to medium ranges forecast skill over Africa. Over the Sahel, the supply of humidity is a key feature in the rainfall distribution and mostly a limiting factor to the initiation of deep convection. Therefore, the current study is based on the total column integrated specific humidity, also called precipitable water, to disentangle the important physics involved in the monsoon intra-seasonal variability and more specifically on the synoptic scale. African Easterly Waves (AEW), also known as the main synoptic scale disturbances of the Western African atmosphere during the boreal summer, have been detected and characterized from this "moist" perspective. This study then provides a new approach for studying the coupling between AEW and convection. A joint assessment of both dynamic and diabatic contributions to the AEW growth has been undertaken. Dynamics is, through the baroclinic and barotropic energy transport, a precursor and a predominant mechanism in the layer below the African easterly jet. However, since convection is enhancing, diabatic processes become accounting for a crucial role in the atmospheric circulation through the release of heat as well as the humidity sink. Meanwhile, subgrid convective scale eddies transport a large part of the horizontal momentum, from the surface to the mid-levels. This enhances the midtroposheric cyclonic/anticyclonic circulation of the AEW. Finally, this process-based analysis of the coupling between dynamics and convection provides some useful tools for model assessment and
Keywords: African Research